A study of the vibration signals behavior - Lim Jun, Lun (2013)
Identification of defects in structures and its components is a crucial aspect in decision making about their repair and replacement. This project presents a study on the application of free and force vibration signals on difference surface beam to detect resonance frequency or natural frequency and the statistical characteristics. The well-established statistical parameters such as kurtosis, mean value, standard deviation, RMS and variance are utilized in the study. Free and force vibration experiments are to determine the natural frequency of the beam from the vibration signal and the vibration signal is use to be analysis on statistical analysis. Under ideal conditions, the modal testing method can be used to identify the natural frequency and mode shape, because it more accurate compares to free and force vibration experiment. The effect of surface beam on the performance of the statistical method is also studied. Results from the study show that the statistical parameters are affected by the surface beam due to the change of the beam structure of which have difference natural frequencies